Language contact phenomena in the language use of speakers of German descent and the significance of their language attitudes - Ries, Veronika (Linguistik Online, 2014)
Within the scope of my investigation on language use and language attitudes of People of German Descent from the USSR, I find almost regular different language contact phenomena, such as viel bliny habn=wir gbackt (engl.: 'we cooked lots of pancakes') (cf. Ries 2011). The aim of analysis is to examine both language use with regard to different forms of language contact and the language attitudes of the observed speakers. To be able to analyse both of these aspects and synthesize them, different types of data are required. The research is based on the following two data types: everyday conversations and interviews. In addition, the individual speakers' biography is a key part of the analysis, because it allows one to draw conclusions about language attitudes and use. This qualitative research is based on morpho-syntactic and interactional linguistic analysis of authentic spoken data. The data arise from a corpus compiled and edited by myself. My being a member of the examined group allowed me to build up an authentic corpus. The natural language use is analysed from the perspective of different language contact phenomena and potential functions of language alternations. One central issue is: How do speakers use the languages available to them, German and Russian? Structural characteristics such as code switching and discursive motives for these phenomena are discussed as results, together with the socio-cultural background of the individual speaker. Within the scope of this article I present exemplarily the data and results of one speaker.